2021
DOI: 10.3847/1538-4357/ac25f3
|View full text |Cite
|
Sign up to set email alerts
|

On the Impact of Inclination-dependent Attenuation on Derived Star Formation Histories: Results from Disk Galaxies in the Great Observatories Origins Deep Survey Fields

Abstract: We develop and implement an inclination-dependent attenuation prescription for spectral energy distribution (SED) fitting and study its impact on derived star formation histories. We apply our prescription within the SED fitting code Lightning to a clean sample of 82, z = 0.21–1.35 disk-dominated galaxies in the Great Observatories Origins Deep Survey North and South fields. To compare our inclination-dependent attenuation prescription with more traditional fitting prescriptions, we also fit the SEDs with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 116 publications
(227 reference statements)
1
27
0
Order By: Relevance
“…Our predicted stellar mass is slightly overestimated compared with DG15, who measured the stellar mass using MAGPHYS (Da Cunha et al 2008). This difference is consistent with the study by Doore et al (2021), who found that inclinationindependent SED models could underestimate stellar mass. In addition, the different choices of the simple stellar population library could also impact the measurements of the stellar mass.…”
Section: Applicationssupporting
confidence: 93%
See 1 more Smart Citation
“…Our predicted stellar mass is slightly overestimated compared with DG15, who measured the stellar mass using MAGPHYS (Da Cunha et al 2008). This difference is consistent with the study by Doore et al (2021), who found that inclinationindependent SED models could underestimate stellar mass. In addition, the different choices of the simple stellar population library could also impact the measurements of the stellar mass.…”
Section: Applicationssupporting
confidence: 93%
“…This is unrealistic, since the dust emission spectrum does not depend on inclination angle, while the UV to optical attenuation does. Doore et al (2021) found that including inclination dependence in SED fitting affects the estimation of stellar mass.…”
Section: Introductionmentioning
confidence: 99%
“…Given the morphological variety and multiple components that are apparent for some of our galaxies, we chose to perform our own detailed photometric extraction and SED fitting of the available far-UV-to-mid-IR data to derive physical properties. We made use of the Lightning SED fitting code (see Eufrasio et al 2017), which fits broadband SEDs using a nonparametric star formation history (SFH) model, including prescriptions for attenuation and nebular and dust emission (see Doore et al 2021, for further details). A detailed account of the SED fitting of this sample and its results will be presented in a forthcoming paper (R. T. Eufrasio et al 2022, in preparation); however, for completeness, we describe the salient details and results below.…”
Section: Galaxy Physical Propertiesmentioning
confidence: 99%
“…Given the morphological variety and multiple components that are apparent for some of our galaxies, we chose to perform our own detailed photometric extraction and SED fitting of the available FUV-to-mid-IR data to derive physical properties. We made use of the Lightning SED fitting code (see Eufrasio et al 2017), which fits broadband SEDs using a non-parametric star-formation history (SFH) model, including prescriptions for attenuation and nebular and dust emission (see Doore et al 2021, for further details). A detailed account of the SED fitting of this sample and its results will be presented in a forthcoming paper (Eufrasio et al in-prep); however, for completeness, we describe the salient details and results below.…”
Section: Galaxy Physical Propertiesmentioning
confidence: 99%
“…The SFH model specifies the intrinsic stellar and nebular spectral shape, which is further modified by attenuation by dust and re-emission of the absorbed radiation in the infrared. We modeled the attenuation using a threeparameter, modified Calzetti et al (2000) extinction curve (as described in Eufrasio et al 2017), and dust emission was modeled using Draine & Li (2007) models (with the fiveparameter implementation described in Doore et al 2021).…”
Section: Galaxy Physical Propertiesmentioning
confidence: 99%